Politicised Space and Contentious Youth in Urban Environmentalism in Indonesia - Alam, Meredian (Universitas Negeri Semarang, 2016)
The paper concerns a youth environmental movement in Bandung to save the urban forest Babakan Silawangi. It is proposed that space for protest plays a significant role in social movements such as environmentalism. Public assembly allows activists to voice their political objections and make their discontent known to the citizenry. Yet political space is different to physical place. According to Henri Lefebvre, political space is an assemblage of co-creation by individuals who occupy the space and demonstrate their subjective meanings for it in expression and lived experience. Since the subjective/collective meanings perceived and experienced by the activists are powerfully enacted, the space itself may shape their identity and this study explores those meanings, which are relational, contextual, and spatial.